2019
DOI: 10.1016/j.matchemphys.2018.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Fcc→bcc→hcp successive phase transformations in the strained ultrathin copper film: A molecular dynamic simulation study

Abstract: The phase transformation behaviors of ultrathin Cu film under uniaxial tensile stress are investigated using molecular dynamic simulation. With the stress increasing, Cu film undergoes a successive phase transformation, i.e. firstly fcc→bcc, then bcc→hcp. The phase transformation process is very fast and thorough, i.e., all parents phase can transit into the new phase almost instantaneously. The crystallography mechanisms of two martensitic transformations are exactly corresponding to Bain and Burgers mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 54 publications
1
7
2
Order By: Relevance
“…The parallel relationship between the {1 1 1} pole figure of α-Fe and the {1 1 0} pole figure of γ-Fe was observed. It meant that there was a Bain relationship between the γ-Fe grain of the transition layer and α-Fe of the substrate [ 29 ]. The lattice relationship of the γ-Fe and α-Fe which has a Bain relationship is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The parallel relationship between the {1 1 1} pole figure of α-Fe and the {1 1 0} pole figure of γ-Fe was observed. It meant that there was a Bain relationship between the γ-Fe grain of the transition layer and α-Fe of the substrate [ 29 ]. The lattice relationship of the γ-Fe and α-Fe which has a Bain relationship is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the tensile process, the dislocation is the result of the irregular movement of atoms, which destroys the original atomic structure and generates new structural types. In FCC structure metals, tensile load makes the atoms move continuously, the original structure is destroyed and dislocations are generated, the phase transformation occurs in the material and FCC structure changes to HCP structure [29]. Moreover, from Figure 7, we observed the generation of twins, which is the result of the cross-slip of the HCP structure during the stretching process.…”
Section: Effect Of Strain Rate On Properties Of Nanopolycrystalline Cu-sn Alloymentioning
confidence: 89%
“…Among these theories, the Bain mechanism has been found to be the most common theory for describing the phase transformation process of FCC→BCC Cu [47][48][49], accomplished by the shortest and simplest movement of atoms. During phase transformation of FCC Cu, deformation along one of the [100] directions results in reverse strain along the other two mutually orthogonal directions, i.e., along the [010] and [001] directions [62]. A recent study has indicated that the gradual increase in strain amount till 9.4% changes the lattice parameter along these [100] type directions marginally, while the applied strain of 12.4% significantly alters the lattice spacing along these directions, and it has been found that the initial lattice constant of FCC Cu (i.e., 0.3615 nm) changed to 0.286 nm along [100] direction in transformed BCC Cu lattice [62].…”
Section: Discussionmentioning
confidence: 99%
“…During phase transformation of FCC Cu, deformation along one of the [100] directions results in reverse strain along the other two mutually orthogonal directions, i.e., along the [010] and [001] directions [62]. A recent study has indicated that the gradual increase in strain amount till 9.4% changes the lattice parameter along these [100] type directions marginally, while the applied strain of 12.4% significantly alters the lattice spacing along these directions, and it has been found that the initial lattice constant of FCC Cu (i.e., 0.3615 nm) changed to 0.286 nm along [100] direction in transformed BCC Cu lattice [62]. Hence, in the present study, the formation of BCC lattice configuration in regions within Cu precipitates possibly followed the similar crystallographic mechanism for transition from FCC to BCC structure, as can be seen for the BCC lattice structure along [100] direction in the FFT of Figure 9c.…”
Section: Discussionmentioning
confidence: 99%